2005
DOI: 10.1098/rspb.2004.2959
|View full text |Cite
|
Sign up to set email alerts
|

A parasite-mediated life-history shift in Daphnia magna

Abstract: The impact of parasitism on host populations will be modulated by both genetic variation for susceptibility, and phenotypically plastic life-history traits that are altered to lessen the fitness consequences of infection. In this study we tested for life-history shifts in the crustacean Daphnia magna following exposure to the horizontally transmitted microsporidian, Glugoides intestinalis. In two separate experiments, we exposed hosts to parasite spores and measured their fecundity relative to controls. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 33 publications
6
86
2
1
Order By: Relevance
“…A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18]. In our study, however, calling activity did not increase in all infected frogs; we found that infected frogs in relatively poor condition were less likely to call than uninfected frogs.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18]. In our study, however, calling activity did not increase in all infected frogs; we found that infected frogs in relatively poor condition were less likely to call than uninfected frogs.…”
Section: Discussioncontrasting
confidence: 49%
“…Both male and female hosts can compensate for an increased risk of mortality imposed by an infection by increasing their investment in earlier reproduction. For example, among female hosts, Tasmanian devils (Sarcophilus harrisii) infected by a transmissible cancer mature and breed earlier [12], and crickets (Acheta domesticus) infected by a bacterium, and water fleas (Daphnia magna) infected by a microsporidian lay more eggs [13,14]. Among male hosts, frogs (Lithobates pipiens) infected by a fungus increase sperm production [15], flies (Drosophila nigrospiracula) infected by a parasitic mite, and amphipods (Corophium volutator) infected by trematodes increase reproductive effort [16,17], and beetles (Tenebrio molitor) infected by tapeworms provide higher quality nuptial gifts to their mates, thus increasing egg production [18].…”
Section: Introductionmentioning
confidence: 99%
“…(50) Ultimately, however, changes in reproductive output cannot be taken as evidence of immune response; at best it can be seen as evidence for a shift in the life history strategy of D. pulex, as in fact reported in a later study of fecundity compensation in the D. pulex/Glugoides intestinalis host/ parasite system. (12) Fecundity compensation is a wellestablished principle in the field of parasitology (51,52) where it has been argued to be an energetically conservative evolutionary solution to the problem presented by the hostparasite evolutionary 'arms race'. There would be some advantage to the mothers as earlier reproduction gives her offspring a small lead over uninfected con-specifics in gaining first access to resources and enabling them to live long enough to reproduce themselves, irrespective of the risk of later infection.…”
Section: Innate Specificitymentioning
confidence: 99%
“…They cannot therefore offer a general new concept that can be applied across a range of invertebrate taxa. (10) reproductive isolation, (11) a switch in life-history strategy, (12) or immune responses to infection. (13) Similarly there are a number of components which contribute to the virulence of any pathogen including the production of virulence factors, (14) quorum sensing interactions (15) and competition with homologous and heterologous parasites for limited host resources.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are three possible evolutionary explanations for pathogen-mediated changes in offspring: (i) they reflect adaptive manipulation beneficial to the pathogen [40][41][42], (ii) they are the inevitable sideeffects of the cost of combating disease [43,44], or (iii) they are adaptive responses to infection by the host ensuring their own reproductive success and that of their offspring [1]. An example of a transgenerational effect that might benefit a parasite is seen in flea-infested great-tits (Parus major), which produce fledglings that disperse shorter distances than healthy birds, and are more likely to be recruited to the local population, providing more nearby future hosts for the parasite [45].…”
Section: Introductionmentioning
confidence: 99%